Hematological Patterns of Anemia in Geriatric Patients - M, Choukimath S; P, Adithyan; Giriyan, Sujata S (Annals of Pathology and Laboratory Medicine, 2019)
Background: Anemia in the elderly is a significant health problem in India and many parts of the World, since it signifies an underlying disease and is associated with poor clinical outcomes. In elderly patients, in whom anemia has a higher prevalence; neither the hemoglobin threshold for concern nor the identity of the anemia causing disease is easily established. Hematological patterns of anemia in elderly are manifold, hence, this study was undertaken to determine them Methods: The present study was conducted on a sample size of 350 patients who were 60 years and above and clinically diagnosed as anaemic. Routine haematological investigations including Peripheral blood smear examination and complete haemogram were done. Special investigations like Bone-marrow examination, Iron studies, Stool and Urine examination were done wherever possible. Result: In the present study Males were more affected than females and patients in the age group of 60-69 years were affected the most. Normocytic normochromic anemia was the most common morphological type of anemia and chronic diseases were the commonest etiological factors. Conclusion: Despite modern diagnostic advances, geriatric anemias still remain under-reported and inadequately investigated; necessitating evaluation of even mild anemias. Prompt diagnosis and definite categorization helps in appropriate management of anemias.